Forming the content of education with the account of the principle of science at the end of the ХІХ - the beginning of the XX century - Tatyana B. Kuzyomа (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the study of various approaches to the content of education in higher educational institutions of the Russian Empire at the end of the 19th and beginning of the 20th century, taking into account the principle of scientific character. The purpose of the article is to consider the specifics of the formation of the content of education in the practice period of the institutes of the Russian Empire, taking into account the ways of implementing the principle of scientific character. The government’s policy towards universities was characterized, the main features of which were centralism and regulation. The main reasons for the regress of the content of higher education are defined: formalism, excessive centralization, lack of academic freedom. Detailed attention is paid to personnel problems and shortcomings in the structures of the universities of the Russian Empire. The ways of realization of the scientific principle in the practice of higher educational institutions of the period under investigation are detailed: comprehensive improvement of the content of education (careful selection of the content of scientific disciplines which are taught in the institutes, obligatory consideration of the logic of science itself and the logic of teaching, presentation of new facts according to scientific hypotheses and theories), organization of educational and cognitive work of students (the use of progressive methods of teaching aimed at developing scientific interest, the formation of skills of scientific knowledge), organization of research work of students (attraction to work in scientific circles, societies, scientific projects of higher education departments). New approaches to the formation of the content of education are considered. Changes in programs and curricula are marked: the introduction of subjects of a scientific and practical orientation, the restructuring of a set of disciplines, the expansion of a number of courses and the emergence of new disciplines, the opening of necessary departments, a new distribution of hours and subjects. The requirements for the content of textbooks are listed: consistency, scientific character, accessibility.